ICare-ACS (Improving Care Processes for Patients With Suspected Acute Coronary Syndrome): A Study of Cross-System Implementation of a National Clinical Pathway. Issue 4 (23rd January 2018) - Than, Martin P.; Pickering, John W.; Dryden, Jeremy M.; Lord, Sally J.; Aitken, S. Andrew; Aldous, Sally J.; Allan, Kate E.; Ardagh, Michael W.; Bonning, John W.N.; Callender, Rosie; Chapman, Laura R.E.; Christiansen, Jonathan P.; et al.
Abstract : Background: Efforts to safely reduce length of stay for emergency department patients with symptoms suggestive of acute coronary syndrome (ACS) have had mixed success. Few system-wide efforts affecting multiple hospital emergency departments have ever been evaluated. We evaluated the effectiveness of a nationwide implementation of clinical pathways for potential ACS in disparate hospitals. Methods: This was a multicenter pragmatic stepped-wedge before-and-after trial in 7 New Zealand acute care hospitals with 31 332 patients investigated for suspected ACS with serial troponin measurements. The implementation was a clinical pathway for the assessment of patients with suspected ACS that included a clinical pathway document in paper or electronic format, structured risk stratification, specified time points for electrocardiographic and serial troponin testing within 3 hours of arrival, and directions for combining risk stratification and electrocardiographic and troponin testing in an accelerated diagnostic protocol. Implementation was monitored for >4 months and compared with usual care over the preceding 6 months. The main outcome measure was the odds of discharge within 6 hours of presentation Results: There were 11 529 participants in the preimplementation phase (range, 284–3465) and 19 803 in the postimplementation phase (range, 395–5039). Overall, the mean 6-hour discharge rate increased from 8.3% (range, 2.7%–37.7%) to 18.4% (6.8%–43.8%). The odds of being discharged within 6 hours increased after clinical pathway implementation. The odds ratio was 2.4 (95% confidence interval, 2.3–2.6). In patients without ACS, the median length of hospital stays decreased by 2.9 hours (95% confidence interval, 2.4–3.4). For patients discharged within 6 hours, there was no change in 30-day major adverse cardiac event rates (0.52% versus 0.44%; P =0.96). In these patients, no adverse event occurred when clinical pathways were correctly followed. Conclusions: Implementation of clinical pathways for suspected ACS reduced the length of stay and increased the proportions of patients safely discharged within 6 hours. Clinical Trial Registration: URL:https://www.anzctr.org.au/ (Australian and New Zealand Clinical Trials Registry). Unique identifier: ACTRN12617000381381. Abstract : Supplemental Digital Content is available in the text.